An algorithm to check balance property of a design - Rashid Ahmed; M. Yousuf Aziz; M. H. Tahir (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2013)
Balance incomplete block design and neighbor balanced deigns have their own importance in the field experiments such as agriculture, horticulture and forestry, etc. In the literature, there are several algorithms to construct the neighbor balanced designs but in this study, an algorithm is developed to check whether a given design is (i) a balanced incomplete block design, (ii) a neighbor-balanced, if so up to which order. This algorithm is coded in Visual C++.
Keywords: 330; balanced incomplete designs; first order neighbor balanced designs; second order neighbor designs; incidence matrix